Factors that Influence the Assesment of the Level of Patient Visits in Outpatient Installantions - Utami, Lia Wahyu; Purwaningsih, Purwaningsih; Ni'mah, Lailatun (Universitas Airlangga, 2019)
Introduction: The number of general patient visits in outpatient installations over the past 3 months has decreased significantly. So that hospital revenue is reduced. The purpose of this study was to determine factors for decreasing outpatient visits.Method: This study was an observational study with a cross-sectional approach. The population in this study were general patients who visited outpatient as many as 100 respondents with sampling techniques with consecutive sampling techniques. The inclusion criteria set are general patients who can communicate well; general patients seeking outpatient treatment; the patient is not illiterate; general patients with good awareness; and patients with age criteria> 13 years, if the patient is still stretched 13-17 years old is filled in by parents, while exclusion criteria are outpatients with decreased consciousness. The independent variable in this study included the characteristics of outpatients visiting the Outpatient Installation. While the dependent variable in this study is the patient's assessment of provider factors which include officers (attitutude, knowledge, and practice), facilities and infrastructure, rates, and registration flow based on the service triangle assessment. This study uses descriptive analysis using a frequency distributive table.Results: The results show that the assessment of strategies, systems and human resources on the assessment of provider factors including rates, officers, registration flow, and facilities and infrastructure. In terms of officers, the tariff, registration flow get a good rating of> 75%. Whereas in the facilities and infrastructure, a good assessment> 75% is in the waiting room, while in the outpatient and check the assessment is not good at 54% and 61%.Conclusion: Factors for the provision of facilities and infrastructure (Provider) greatly affect visits from general patients in outpatient installations. It is expected that in future studies it is expected to be able to find updates or applications based on the Android Operating System or Iphone Operathing System that can be used as reminders and monitor patient schedules for hospital visits.